Penerapan Rapid Application Development (RAD) Pada Perancangan Aplikasi Tracer Study Berbasis Android - Aryani, Diah; Malabay, Malabay; Ariessanti, Hani Dewi (STKIP PGRI Sumatera Barat, 2020)
Higher education is an educational provider that plays a role in producing quality graduates, tracking the absorption of graduates that are relevant to their scientific fields is needed in collecting graduate data. However, Tracer Study management still has problems, especially when searching for data from its alumni so that in this study, an Android-based Tracer Study application design was carried out with the application of Rapid Application Development (RAD) which aims to provide convenience in tracing and managing alumni data at a college. This study uses the RAD software development method, the purpose of this research is to design the Tracer Study application which aims to make it easier for universities to trace alumni data and to get feedback from alumni which can be used as information for universities in making decisions and evaluating in improving education delivery that can produce graduates with the appropriate competencies. with the needs of the industrial world.Keywords: Tracer Study, android, Rapid Application Development, application, Unified Modeling Language